2015
DOI: 10.1002/mnfr.201500334
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine programming of lipid metabolic alterations in the heart of the offspring of diabetic rats is prevented by maternal diets enriched in olive oil

Abstract: Relevant alterations in cardiac lipid metabolism were evident in the adult offspring of a mild diabetic rat model, and regulated by maternal diets enriched in olive oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
1
9
0
2
Order By: Relevance
“…Importantly, the increased levels of prooxidant and proinflammatory markers we observed in the embryo from mild diabetic rats during early organogenesis have also been observed in fetuses (Pustovrh et al, 2005), placentae (Martinez et al, 2012) and in the postnatal heart (Capobianco et al, 2015), suggesting that embryonic alterations may affect later development.…”
Section: Discussionmentioning
confidence: 52%
“…Importantly, the increased levels of prooxidant and proinflammatory markers we observed in the embryo from mild diabetic rats during early organogenesis have also been observed in fetuses (Pustovrh et al, 2005), placentae (Martinez et al, 2012) and in the postnatal heart (Capobianco et al, 2015), suggesting that embryonic alterations may affect later development.…”
Section: Discussionmentioning
confidence: 52%
“…In the current study, supplementation of the diet with 6% olive oil in F1 pregnant offspring from rats with mild diabetes was not able to prevent the induction of GDM, as shown by the increased maternal and fetal plasma glucose levels at term. Similarly, we previously found that an olive oil‐supplemented diet in F0 pregnant rats with mild diabetes did not normalize maternal blood glucose levels and did not prevent development of type 2 diabetes associated with aging in the nonpregnant F1 offspring . In a recent study in pregnant women, a Mediterranean diet added with extra virgin olive oil and pistachios reduced the incidence of GDM and fetal overgrowth .…”
Section: Discussionmentioning
confidence: 84%
“…From day 1 to day 21 of the F1 pregnancy, the offspring from rats with mild diabetes and controls were fed with: a) a standard diet (commercial rat chow) or b) a standard diet (commercial rat chow) supplemented with 6% olive oil. The diet composition, analyzed by gas chromatography‐mass spectrometry as previously was: a) Standard diet (g per 100 g): carbohydrates (50); proteins (25); fat (5), major fatty acids 16:0 (0.58), 18:0 (0.16), 18:1 n‐9 (1.27), 18:2 n‐6 (1.99), and 18:3 n‐3 (0.73), and b) olive oil‐supplemented diet (g per 100 g): carbohydrates (48); proteins (24); fat (11), major fatty acids 16:0 (1.55), 18:0 (0.26), 18:1 n‐9 (5.77), 18:2 n‐6 (2.41), and 18:3 n‐3 (0.57). The F1 pregnant rats were euthanized at day 21 of gestation.…”
Section: Methodsmentioning
confidence: 99%
“…PPARs are nutrigenomic agents, being monounsaturated fatty acids (MUFAs, the main components of olive oil), PPARs endogenous ligands 9,10 . In experimental models of diabetes and pregnancy, our previous studies have shown that diets enriched in extra virgin olive oil (EVOO) lead to antiinflammatory effects, as shown by the ability of these diets to prevent increased levels of proinflammatory cytokines, nitric oxide overproduction, and matrix metalloproteinases (MMPs) overexpression in placentas, embryos and different foetal organs 11‐16 . Studies have also shown that although maternal EVOO‐dietary treatments do not prevent programming of metabolic diseases in the offspring of diabetic animals, this treatment reduces the levels of proinflammatory markers in the offspring's heart and prevents hypertriglyceridemia in the adult offspring of diabetic rats 11,16 …”
Section: Introductionmentioning
confidence: 99%